Terje Vigen Based on a Poem by Henrik Ibsen - Bye, Matti; Holmgren, Kristian
The original poem is not widely known in this country, and one who has not read it cannot say how much of it has been preserved in the motion picture, but "A Man There Was," taken by itself, is impressive in many of its scenes, acted with well-directed vigor by Mr. Seastrom, and forceful despite its occasional indulgence in too much sentimentality and moralizing. Its story is of a Scandinavian sailor who loses his wife and child through the hardness of an enemy, but has an opportunity for revenge years later, when his enemy's wife and child are in his power. He may let them drown or be the means of saving them. After bringing them almost to their death he relents and permits their rescue. [movies.nytimes.com]
Keywords: DVD-Video